Metaverse platform as a new culture: analysis of fomo phenomenon in college students - Junaidi, Junaidi; Liza, Ledya Oktavia; Ardiya, Ardiya; Situmorang, Dominikus David Biondi (COUNS-EDU: The International Journal of Counseling and Education, 2024)
The phenomenon of Fear of Missing Out (FoMO) is a notable impact associated with the usage of these platforms metaverse. This study focuses on assessing the FoMO levels among university students and examines variations based on age, gender, and specific FoMO indicators. Adopting a quantitative methodology with a descriptive approach, the research involved 346 students aged 18 to 24. The findings revealed that the highest level of FoMO was classified as high, at 59.5%. Among these, female students exhibited a higher prevalence of FoMO at 68%, compared to their male counterparts at 48%, who fell into the medium category. The most significant FoMO indicator was the urge to check updates on social media. The study concluded that FoMO levels among students are predominantly high, with minor age-related variations. Gender-wise, a distinction was noted where females showed higher levels of FoMO than males. The compulsion to monitor social media updates emerged as the most prominent FoMO descriptor.